A 60 000 year Greenland stratigraphic ice core chronology - Siwan Davies (Climate of the Past, 2008)
The Greenland Ice Core Chronology 2005 (GICC05) is a time scale based on annual layer counting of high-resolution records from Greenland ice cores. Whereas the Holocene part of the time scale is based on various records from the DYE-3, the 5 GRIP, and the NorthGRIP ice cores, the glacial part is solely based on NorthGRIP records. Here we present an 18 kyr extension of the time scale such that GICC05 continuously covers the past 60 kyr. The new section of the time scale places the onset of Greenland Interstadial 12 (GI-12) at 46.9±1.0 kyr b2k (before year AD 2000), the North Atlantic Ash Zone 2 layer in GI-15 at 55.4±1.2 kyr b2k, and the onset of GI-1710 at 59.4±1.3 kyr b2k. The error estimates are derived from the accumulated number of uncertain annual layers and can be regarded as 1σ uncertainties. In the 40–60 kyr interval the new time scale has a discrepancy with the Meese-Sowers GISP2 time scale of up to 2.4 kyr, whereas GICC05 compares well to the dating of the Hulu Cave record with absolute age diﬀerences of less than 800 years throughout the 60 kyr period. The 15 new time scale is generally in close agreement with other independently dated records and reference horizons, such as the Laschamp geomagnetic excursion and the Kleegruben speleothem record from the Austrian Alps, suggesting high accuracy of both event durations and absolute age estimates.